ANALISIS PELAYANAN PUBLIK DI KELURAHAN KUNCIRAN KECAMATAN PINANG KOTA TANGERANG - Saifullah, Ricki; Kurniawan, Bambang; Sugara, Asep (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The objectives of this research are: 1) Knowing the role of officials' responsibilities in improving public services in Kunciran Village, Pinang District, Tangerang City, 2) Knowing the supporting and inhibiting factors in improving public services, 3) Knowing the efforts made by officials to improve public services. Seeing the purpose of this study, the research method used is a qualitative method. The informants used as sources of information in this research were the secretary of Kunciran sub-district, Pinang District, Tangerang City, head of the governance section, head of the economic and development section, the general public and head of the community association. Data collection techniques were carried out using interview, observation and documentation techniques. Data analysis was carried out by means of data reduction, data display and drawing conclusions from the results of interviews with research informants. The conclusions of this research are 1) Apparatus in Kunciran Village, Pinang District, Tangerang City have awareness as state servants who have a moral, personal and social role to be responsible in carrying out their duties and functions in providing services to the community, 2) Supporting factors in improving quality public services, namely that the apparatus has moral, personal and social awareness in providing services in a transparent, accountable, participatory, conditional manner, fulfills the rights of service recipients and pays attention to the balance of rights and obligations of service recipients and the public has the awareness to participate in the implementation of public services, while the inhibiting factor is that there are people who do not know clearly about the procedures for service requirements, 3) Efforts made by the apparatus in Kunciran Village, Pinang District, Tangerang City to improve services, namely by making computerized improvements to the village administration and providing public services in a transparent, accountable manner. , conditional, participatory, non-discriminatory and pays attention to the balance of rights and obligations in providing services to the community